2014
DOI: 10.1007/s12012-014-9253-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Myocardial Infarct Size on Cardiac Reserve in Rhesus Monkeys

Abstract: Evaluation of cardiac reserve under myocardial infarction in patients is important for prognosis. However, this evaluation is difficult to be done due to high risk for mortality in patients with severe myocardial infarction. The present study was undertaken using non-human primate model as a substitute for humans to investigate the relationship between cardiac reserve and myocardial infarct size. Rhesus monkeys of 2-3 years old (n = 27) were subjected to left anterior descending artery ligation to introduce ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…As described in our previous studies, 14,15 the heart of monkeys was exposed via the left fourth intercostal thoracotomy. The LAD artery was occluded for 1 min followed by a 5 min reperfusion, and this occlusion-reperfusion cycle was repeated 3 times before the eventual ligation.…”
Section: Induction Of Myocardial Ischemic Infarctionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in our previous studies, 14,15 the heart of monkeys was exposed via the left fourth intercostal thoracotomy. The LAD artery was occluded for 1 min followed by a 5 min reperfusion, and this occlusion-reperfusion cycle was repeated 3 times before the eventual ligation.…”
Section: Induction Of Myocardial Ischemic Infarctionmentioning
confidence: 99%
“…12 Our recent studies demonstrated that the Rhesus monkey model of myocardial ischemic infarction recaptured the manifestations in human myocardial infarction. [13][14][15] The present study was undertaken employing a Rhesus monkey model of myocardial ischemia induced by left anterior descending (LAD) artery ligation to examine the relationship between the changes in HIF-1 and its regulated gene expression and the depressed capillary density following a long-term ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…As described in our previous studies [ 27 , 28 ], the monkey’s heart was exposed via a left fourth intercostal thoracotomy incision (4–5 cm) in the chest wall. The LAD was occluded for 1 min followed by a 5 min reperfusion, and this occlusion-reperfusion cycle was repeated 3 times before the eventual permanent ligation.…”
Section: Methodsmentioning
confidence: 99%
“…It is obvious that ligation at different levels along the LAD artery will differentially affect areas of the left ventricle. (7,15) What's more important, the LAD artery is branched, quite different from rodents. It is particularly noticed that blood vessels branched from the LAD artery in monkeys display an irregular distribution, thus affecting the consistency of ischemic infarction area of the ventricle.…”
Section: Introductionmentioning
confidence: 99%